MURAL DAN DESAIN LOGO SARI KEDELAI & SUSHI (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2019)
This article contains the creation of mural and food products design made by KWU division. Thepurpose of this article is to improve product quality on the design of KWU division product output.This research is done by method. From this article can be concluded people interested in makingsushi and soymilk products. So, the design created by KWU division is beneficial to improve productsmanaged by the community.